2016
DOI: 10.1308/rcsann.2016.0181
|View full text |Cite
|
Sign up to set email alerts
|

A comparative audit of gunshot wounds and stab wounds to the neck in a South African metropolitan trauma service

Abstract: Introduction The aim of this comparative study of gunshot wounds (GSWs) and stab wounds (SWs) to the neck was to quantify the impact of the mechanism of injury on the outcome and management of penetrating neck injury (PNI). Methods A prospective trauma registry was interrogated retrospectively. Data were analysed pertaining to demographics and injury severity score (ISS), physiology on presentation, anatomical site of wounds and injuries sustained, investigations, management, outcome and complications. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 23 publications
(46 reference statements)
0
20
0
5
Order By: Relevance
“…The numbers treated here are also well below those seen in some centres internationally. For example, a study in a trauma centre in Pietermaritzburg, South Africa, recorded 462 neck stab wounds in 46 months, with a mortality of 2% [ 12 ]. An analysis of 13 years’ data from a trauma centre in Los Angeles, USA, recorded 606 PNIs [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The numbers treated here are also well below those seen in some centres internationally. For example, a study in a trauma centre in Pietermaritzburg, South Africa, recorded 462 neck stab wounds in 46 months, with a mortality of 2% [ 12 ]. An analysis of 13 years’ data from a trauma centre in Los Angeles, USA, recorded 606 PNIs [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…This decision making is intimately related to both the zone of injury in the neck (Table 2) and the mechanism of injury as gunshot wounds (GSWs) are far more destructive than SWs and some authors will routinely image all GSWs to the neck. 11…”
Section: Resuscitationmentioning
confidence: 99%
“…2,9 In one study of 510 PNI patients, 76% underwent CTA and if CTA did not show an injury then it could be safely concluded that there was no injury. There is however a definite risk of a false positive results and this must be borne in mind when planning management of an injury seen on CTA; 11 the use of CTA as a screening modality for asymptomatic patients is probably not justified. 21,22
Figure 2.(a) Filling defect in the proximal segment of the right common carotid artery, zone 1 and (b) pseudoaneurysm of the right common carotid artery, zone 2.
…”
Section: Vascular Investigationsmentioning
confidence: 99%
“…The absence of management guidelines for pharyngoesophageal injuries is due to the paucity of available literature, particularly in regard to operative intervention. Most recommendations originate from studies on penetrating neck trauma (68, 1416). In a review of eight studies with 179 patients that included penetrating, blunt, and iatrogenic injuries, 105 underwent surgical management and the remaining 74 were observed.…”
Section: Discussionmentioning
confidence: 99%